1991
DOI: 10.1111/j.1532-5415.1991.tb03593.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Postural Hypotension in a Community Sample of Elderly Blacks and Whites

Abstract: Postural hypotension is thought to be prevalent among the elderly, but few community-based studies of this condition have been conducted. In addition, little is known about postural hypotension in blacks despite well documented racial differences in hypertension and stroke. Data on 659 elderly (greater than or equal to 60 years of age) participants in a survey of two rural, biracial townships were analyzed to describe the frequency and correlates of postural hypotension. Twelve percent of the 659 adults experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
1
4

Year Published

1999
1999
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 27 publications
3
26
1
4
Order By: Relevance
“…[1][2][3]5,6,10,11,13,14 In the current report, lower BMI was positively related to an excess in the odds of OH. Although findings were adjusted for age, hypertension, diabetes, cigarette smoking, total cholesterol, HDL cholesterol, and triglycerides, other unknown comorbidities in leaner individuals are likely to have contributed to this finding.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…[1][2][3]5,6,10,11,13,14 In the current report, lower BMI was positively related to an excess in the odds of OH. Although findings were adjusted for age, hypertension, diabetes, cigarette smoking, total cholesterol, HDL cholesterol, and triglycerides, other unknown comorbidities in leaner individuals are likely to have contributed to this finding.…”
Section: Discussionsupporting
confidence: 54%
“…In the Systolic Hypertension in the Elderly Project (SHEP) 13 and the Cardiovascular Health Study, 4 no significant differences were observed in the prevalence of OH between ethnic groups, mainly composed of Caucasian and Black individuals. In a survey in two rural communities, however, prevalence of OH was twice as common in elderly Caucasians as compared to Blacks, 14 while in the ARIC study, 1,2 systolic OH was observed to be higher in Blacks than in Caucasians.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…12 Orthostatic hypotension (OH), or a large decrease in blood pressure in response to a change in posture, has been inconsistently associated with elevated blood pressure in cross-sectional studies. [13][14][15][16] This study examined whether DSBP (increases and decreases) and OH were predictive of hypertension in a normotensive, bi-ethnic population-based sample of middle-aged men and women, followed over a period of approximately 6 years. As blood pressure reactivity is sometimes reported to be higher among those with higher levels of resting blood pressure, 17 we also tested the hypothesis that associations would be stronger among those with higher levels of baseline, seated blood pressure.…”
Section: Introductionmentioning
confidence: 99%